2006
DOI: 10.3171/jns.2006.104.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Tissue plasminogen activator in chronic subdural hematomas as a predictor of recurrence

Abstract: Patients harboring CSDHs with high TPA concentrations on sampling at the initial surgery have a relatively high probability of recurrence and require follow up with computerized tomography scanning. Angiogenic factors, such as HGF and VEGF, might be candidate markers of CSDH enlargement but are not useful as predictors of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…In this respect, it has been shown that the hematoma fluid contains high concentrations of coagulation factors (plas minogen activator) 14 and inflammatory factors (vascular endothelial growth factor), 33 and both factors are shown to be predictive of recurrence. 19,30 These mechanisms remain speculative, however.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it has been shown that the hematoma fluid contains high concentrations of coagulation factors (plas minogen activator) 14 and inflammatory factors (vascular endothelial growth factor), 33 and both factors are shown to be predictive of recurrence. 19,30 These mechanisms remain speculative, however.…”
Section: Discussionmentioning
confidence: 99%
“…When CSF or extravasated blood gathers into the restricted area of the dural border cell layer [3][4][5], it evokes local aseptic inflammatory- [6][7][8][9][10] and inflammationinduced angiogenic reactions [8,[11][12][13][14][15][16][17]. The result is production of granulation tissue, consisting of numerous newly formed and permeable blood vessels, inflammatory cells, proliferating fibroblasts corresponding to ''boundary cells'' and smooth muscle cells, that takes place primarily on the inner dural surface [3,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This results in formation of a capsule, also called CSDH neomembranes, within 3 to 4 weeks after trauma. These processes are accompanied by abnormality in the local coagulo-fibrinolytic system [12,[21][22][23][24][25]. Thus, CSDH is currently considered a circumscribed chronic self-perpetuating inflammatory disorder that involves the dura mater; however, local immune responses in this disorder are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…19) On the other hand, CSDH is also associated with an imbalance of factors involved in the regulation of coagulation and fibrinolysis. 8,10) The combination of fragile and permeable microvessels with coagulopathy is believed to be one of the causes of CSDH.…”
Section: Introductionmentioning
confidence: 99%